Pathways to aggression: A factorial survey of “Routine conflict” - Kennedy, Leslie W. (Journal of quantitative criminology, 1994)
Based on data collected in 1994 from a factorial survey of 2052 respondents, this paper examines how routine conflict may escalate into aggression taking into account social context and characteristics of the victim and offender. Following Luckenbill and Doyle's (1989) suggestion, we developed a series of scenarios to examine the influence of structural position on the emergence of disputes and the legitimation of aggression. The analysis reveals a direct relationship between the intensity of an attack with the emergence of a dispute and the legitimation of aggression. Results indicate that situational aspects of structural position do not extend beyond sex differences. This emphasizes the generalizing effect of male on male confrontation in the legitimation of aggression. The strengths and limitations of scenario-based research for understanding violence in society are discussed.